Fees and assistance as basic element in franchise business in Malaysia - Yaacob, Nurli; Naiimi, Nasri; Kasim, Munirah (Global Academic Excellence, 2018)
The development of the franchise business in Malaysia is supported by the existing legal framework and institutional framework. Through the provisions of the Franchise Act 1998, the basic elements of the franchise business are formed. Among them are payment of fees and assistance given by the franchisor to the franchisee. Both elements are sometimes not complied with by both parties. Therefore, this article aims to discuss the basic elements of fees and assistance in the franchise business with its Islamic perspectives in brief. The method used in this study is a legal study supported by interviews with the franchisor. The findings show that there is a clear provision in the Franchise Act 1998 on fees and assistance. The findings from the interviews on the franchisor also show that all of them are in compliance with the provisions of the law on this matter.